Livestock and Fish systems analysis for sustainable innovation flagship review and plans - Notenbaert, An Maria Omer (International Livestock Research Institute, 2015)
An Notenbaert to the CGIAR Research Program on Livestock and Fish review and planning meeting, 23-26 March 2015